Programas projetivos: uma visão panorâmica dos gregos aos modernos, suas caraterísticas, seus princípios e fundamentos - André Reis Penido (2019)
These writings intend to discuss projective programs, not according to their potentialities as project tools, but according to the historical perspective of the successive elements of culture and knowledge that propitiate and sustain them. As will be seen, as these elements emerge in history also constituting projective principles - essential for projective programs - will be simultaneously before the objects of knowledge that underlie the specific field of knowledge of projective practice or its epistemic field. Considering these perspectives, these writings aim to apprehend the transformations in the time of the ideas that support the projective practices to conclude that the contemporary projective programs are not apt to the critic of the own objects that they propose to constitute. Although not present as a central theme, this rapid panoramic route still allows us to delineate, in a preambular way, enough arguments on which the specific epistemological status for projective practice can be constructed.